Promoted the reduction of Cu2+ to enhance CuOCeO2 catalysts for CO preferential oxidation in H2-rich streams: Effects of preparation methods and copper precursors. (24th August 2017) - Wang, Jing; Pu, Hongping; Wan, Gengping; Chen, Kezhen; Lu, Jichang; Lei, Yanqiu; Zhong, Liping; He, Sufang; Han, Caiyun; Luo, Yongming
Abstract: A series of CuOCeO2 catalyst samples synthesized by using various methods (CuCe-SF-N, CuCe-UGC-N, CuCe-SG-N and CuCe-ST-N) and copper precursors (CuCe-SF-N, CuCe-SF-C, CuCe-SF-A and CuCe-SF-S) were estimated for CO preferential oxidation in H2 -rich streams. It was found that both synthesis routes and copper precursors have an important effect on catalytic behaviors of CuOCeO2 catalyst. Compared to CuCe-UGC-N, CuCe-SG-N and CuCe-ST-N, CuCe-SF-N exhibits the lowest temperature and the widest temperature window for 100% CO conversion (about 50 °C), which should be attributed to synergistic effects of smaller crystallite size, the formation of more Cu + species together with the high ratio of Ce 3+ /(Ce 3+ +Ce 4+ ). Among the four catalysts prepared with different Cu precursors (CuCe-SF-N, CuCe-SF-C, CuCe-SF-A and CuCe-SF-S), the corresponding CO conversions of them are in the order of CuCe-SF-N > CuCe-SF-A > CuCe-SF-C » CuCe-SF-S. The lowest catalytic activity of CuCe-SF-S should be due to the presence of SO4 2− species covered on the surface of the catalyst, which not only results in the formation of the less Cu active species but inhibits the interaction between Cu species and CeO2 . In addition, the optimal CuCe-SF-N catalyst displays relative stability during the 200 h time-on-stream test even in the presence of H2 O and CO2 . Graphical abstract: Highlights: CuOCeO2 catalyst prepared by solvent-free method shows high activity for CO-PROX. Copper precursor plays an important role on the physicochemical properties of the catalysts. Cu species with small crystallite size and high dispersion show excellent performance.